Homelessness among young women leaving care - an exploratory study - Wald, Susanne (Cranfield University, 1997)
This study began in 1989 and is about leaving care and youth homelessness among young women. Little was known about young women leaving care, the early transitions of finding and maintaining independent housing, becoming a parent and managing an independent income. The research was exploratory and conducted in two parts. The first part was an 18 month longitudinal study of a cohort of female care leavers in two local authority areas, following their progress from the age of 17 until almost 19. The outcome of the first part was a typology of care leavers. The second part of the PhD consisted of a test of the typology on a larger sample by surveying a group of professionals through a mailed questionnaire. There were differences in the way the sample managed the transition to adulthood. Those who coped with the transition to adulthood more successfully, moved into independence later and in a planned way. They had good personal skills and resilience which was not adversely affected by the framework of existing social policies. Those who struggled with the transition to adulthood experienced homelessness, debts and problems in caring for their children. They had fewer personal skills, less stable support and were affected by existing social policies. Broadly, the typology was confirmed by the questionnaire sample. The study makes recommendations which affect social policies in housing, social security and employment and training and suggests ways in which the typology may assist social work practice in working with young women in care and leaving care.